Emerging Europe and Central Asia - Opportunities for men and women - World Bank (World Bank, 2012)
Europe and Central Asia have suffered a setback in economic growth because of the recent global crisis, which revealed fundamental structural weaknesses previously hidden by the prosperity before the crisis. The major weaknesses are the large savings deficits, the lagging reforms in the social sectors, and the deterioration in competitiveness. Policies can address these weaknesses by taking into account the role of the behavior of firms, public spending on health and education, the consequences of demographic pressures, particularly on pension systems, and the bottlenecks created by skilled labor force shortages. This report reviews the performance of women and men during the past decade in three spheres: human capital, labor markets, and entrepreneurship. Similar to World Development Report 2012 (World Bank 2011a), it looks at the dimensions of endowments and economic opportunities. However, it does not cover issues related to agency, that is, the ability of actors to make independent choices and exercise control over their own actions. The data are analyzed to determine whether women and men are performing well compared with each other, but also how they fare in a global context. The analysis is primarily quantitative and mines various data sets. This is strength of the report because a quantitative analysis can add value by providing some measure of the degree of differences in the outcomes observed. Yet, it is a weakness as well because the outcomes are measured, but not always explained. Consequently, more work is needed in this area, especially qualitative analysis that is followed up by targeted quantitative surveys.